2010
DOI: 10.1007/s10694-010-0156-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fine Water Mist on a Confined Blast

Abstract: A computational, multi-phase, model has been developed to study the interactions between water droplets and radial expansion of a gas cloud in a spherical chamber. Initial conditions for the gas cloud are specified based on chemical equilibrium calculations for the detonation of a high explosive (RDX). Mono-dispersed water droplets are injected at uniform concentration into the chamber prior to the expansion. A Lagrangian model is used to track the breakup of the parent drops near the shock front to form child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 20 publications
3
18
2
Order By: Relevance
“…The suppression results obtained for the aluminized explosives, Destex and PBXN-109 confirm thermodynamic and Navier-Stokes calculations that predicted the overpressure would be reduced in the presence of water mist [22]. This is significant because it was suggested that water mist in the chamber would lead to reactions between aluminum and water to form hydrogen.…”
Section: Effects Of Mist On Blastsupporting
confidence: 68%
See 4 more Smart Citations
“…The suppression results obtained for the aluminized explosives, Destex and PBXN-109 confirm thermodynamic and Navier-Stokes calculations that predicted the overpressure would be reduced in the presence of water mist [22]. This is significant because it was suggested that water mist in the chamber would lead to reactions between aluminum and water to form hydrogen.…”
Section: Effects Of Mist On Blastsupporting
confidence: 68%
“…Recent simulations of a 50 lb detonation of high explosive in a 3.5 m radius spherical chamber performed by Ananth et al indeed highlight the significance droplet breakup has on blast suppression [22]. The simulations show that a shock front propagates ahead of the thermal front immediately following the detonation.…”
Section: Effects Of Mist On Blastmentioning
confidence: 94%
See 3 more Smart Citations